Before and After Treatment Quantitative Assessment of Hepatic Steatosis in a Romanian Population Using Magnetic Resonance Liver Spectroscopy - LĂPĂDAT, AM (Curr Health Sci J, 2019)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common liver disease that progressively develops in four stages (steatosis, non-alcoholic steatohepatitis-NASH, fibrosis, cirrhosis). In order to accurately evaluate the amount of fat content inside the hepatocytes, non-invasive imaging studies such as magnetic resonance spectroscopy (MRS) of the liver can be used as an alternative method to the traditional invasive liver biopsy. The main objective of our study was to quantitatively assess hepatic steatosis before and after treatment using liver MRS. The study group included 35 patients diagnosed with NAFLD who freely expressed their agreement to take part in this study. The treatment lasted 6 months and consisted of administering a local commercially available liver protection supplement combined with dietary and lifestyle adjustments. The initial quantitative assessment of the liver fat content using MRS revealed a hepatic lipid accumulation ranging from 15.70% to 68.03%, with a mean value of 41.26%. The subsequent liver MRS performed after 6 months of proper treatment indicated a fat content inside the liver parenchyma ranging from 15.47% to 58.98%, with a mean value of 36.07%. The therapeutic measures that were applied to the patients managed to reduce the amount of fat content inside the liver parenchyma in 24 patients (68.57%), while in 11 patients (31.43%) the results revealed an increase in hepatic lipid content. In conclusion, the current study reached its initial objective and offered a modern approach regarding the pre and post-treatment evaluation of hepatic steatosis using MRS.